(untitled) (International Journal of Built Environment and Sustainability, 2023)
Rail transportation had been receiving more attention in the Government’s effort to enhance the Malaysian economy internationally. Nevertheless, rail projects involve various stakeholders, massive budgets and are susceptible to cost overrun. This paper aims to evaluate the cost influences concerned with rail projects in a developing nation from contractors’ perspectives. The existing studies lack the consideration of the correlation and relationship between the cost influences, which this paper emphasizes. The data collection was performed by distributing questionnaires to 200 cost managers which are quantity surveyors, project managers, and contract executives across the rail projects in Malaysia. The data analysis uses Statistical Package for Social Sciences Version 27 (SPSS V27) and Structural Equation Modelling (SEM). Kaiser-Meyer-Olkin (KMO) measure of sampling adequacy showed appropriate internal consistency of the research instrument, whereas the Confirmatory Factor Analysis (CFA) showed acceptable Goodness-of-Fit Indices (GFI) within the constructs of the structural model. The SEM calibration resulted in 23 significant cost influences which were clustered into five groups of cost influences. Each of the five groups is associated with different parties in construction projects. A notable causative direction was observed in the relationship between the cost influences. Each cost influence can be connected to each project phase based on the PMBOK Guide. This study adds to the various cost management research along the project management of rail construction. It is able to contribute to the policymakers and consultants in strategizing their cost management plans which is crucial, especially in developing countries such as Malaysia. Emphasizing the critical particulars of cost management in rail projects, this paper also delivers its finding based on stakeholder and system aspects in relation to cost management, which can be referred to by any developing country.